The diabetic paradox differs in patients with prediabetes and normal glucose regulation after colorectal surgery - John D. Mannion; Assar Rather; Adrianne Fisher; Margaret McEvilly; Kelly Gardner; Gary Siegelman (BMC Surgery)
Abstract Background Patients without diabetes, composed of those with normal glucose regulation or prediabetes, experience a higher complication rate than patients with diabetes in response to surgical stress. It is unknown if excess complications occur equally among all patients without diabetes and if hyperglycemia or inflammatory indices are the best markers of postoperative complications. Methods In this retrospective review of medical records, postoperative infections, acute kidney injury (AKI), and composite in-hospital complications were measured after colorectal surgery in patients with varying states of preoperative glucose metabolism. The effects that postoperative hyperglycemia (glucose > 180 mg/dl) and inflammation (systemic inflammatory response index (SIRI) had on the complications within each group were examined. Results Hyperglycemic patients without diabetes experienced excess infections (P = 0.028), AKI (P = 0.023), and in-hospital complications ( P = 0.009) in comparison with patients with diabetes. However, excess infections occurred exclusively in patients with normal glucose regulation (P = 0.039), not those with prediabetes (P = 0.166), and were associated with inflammation (P = 0.020) and not severe hyperglycemia on multivariable analysis. In contrast, exaggerated AKI was found only in patients with prediabetes (P = 0.005), not with normal glucose regulation (P = 0.296), and was independently associated with elevated morning glucose values (P = 0.000). Conclusions Excess complications among patients without diabetes are concentrated in patients with normal glucose regulation or prediabetes. Inflammatory markers are a better predictor of infections, while early hyperglycemia reflects a process injurious to kidney function.